PENINGKATAN PENGETAHUAN SISWA SEKOLAH DASAR DI BANJARMASIN MELALUI PENYULUHAN TENTANG PENCEGAHAN DAN PENANGANAN PERTAMA TENGGELAM - Trifianingsih, Dyah; Dhawo, Maria Silvana; Sitompul, Dania Relina (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Drowning is a serious threat to human life; it has been widely reported that drowning cases result in the deaths of children, followed by teenagers, and then young adults, in all countries. The World Health Organization (WHO) has stated that it is important to create serious policies to address deaths caused by drowning, one of which is to raise awareness regarding the prevention and treatment of drowning victims. This community service aims to increase students' knowledge and skills regarding the prevention cycle and chain of survival for drowning victims. The service was held on May 26, 2023, at SDN 1 Telaga Biru Banjarmasin. The participants comprised 59 students from classes 5A and 5B at SDN 1 Telaga Biru. The method used for health education included talk sessions, discussions, and demonstrations. The media used PPT materials, leaflets, videos, and teaching aids (CPR mannequins). The activity began with providing health education through talk sessions and videos about the concept of drowning, followed by a demonstration of drowning treatment techniques. The activity was evaluated through questionnaires administered at the program's beginning and end, followed by allowing participants to demonstrate drowning management techniques. The results of the community service showed an increase in the average knowledge scores before community service (7.79) and after community service (9.11). Additionally, the observation results indicated that 93.6% of participants could demonstrate first-aid techniques for drowning. This demonstrates a significant change in knowledge and skills related to first aid for drowning victims at SDN 1 Telaga Biru. It is expected that health education will improve elementary school students' ability to prevent, recognizing and providing first aid to drowning victims according to the needs and actions that can be carried out by lay people.